Chemokine receptors CCR6 and CXCR3 are necessary for CD4(+) T cell mediated ocular surface disease in experimental dry eye disease. - Terry G Coursey; Niral B Gandhi; Eugene A Volpe; Stephen C Pflugfelder; Cintia S de Paiva (PLoS ONE, 2013)
CD4(+) T cells are essential to pathogenesis of ocular surface disease in dry eye. Two subtypes of CD4(+) T cells, Th1 and Th17 cells, function concurrently in dry eye to mediate disease. This occurs in spite of the cross-regulation of IFN-γ and IL-17A, the prototypical cytokines Th1 and Th17 cells, respectively. Essential to an effective immune response are chemokines that direct and summon lymphocytes to specific tissues. T cell trafficking has been extensively studied in other models, but this is the first study to examine the role of chemokine receptors in ocular immune responses. Here, we demonstrate that the chemokine receptors, CCR6 and CXCR3, which are expressed on Th17 and Th1 cells, respectively, are required for the pathogenesis of dry eye disease, as CCR6KO and CXCR3KO mice do not develop disease under desiccating stress. CD4(+) T cells from CCR6KO and CXCR3KO mice exposed to desiccating stress (DS) do not migrate to the ocular surface, but remain in the superficial cervical lymph nodes. In agreement with this, CD4(+) T cells from CCR6 and CXCR3 deficient donors exposed to DS, when adoptively transferred to T cell deficient recipients manifest minimal signs of dry eye disease, including significantly less T cell infiltration, goblet cell loss, and expression of inflammatory cytokine and matrix metalloproteinase expression compared to wild-type donors. These findings highlight the important interaction of chemokine receptors on T cells and chemokine ligand expression on epithelial cells of the cornea and conjunctiva in dry eye pathogenesis and reveal potential new therapeutic targets for dry eye disease.